Disease Genes Are Not Patentable: A Rebuttal of McGee - Merz, Jon F. (Cambridge quarterly of healthcare ethics, 1998)
Dr. McGee presents a cogent argument for the patentability of the diagnosis of gene forms that are found to be associated with disease or other phenotypic manifestations. We're convinced he's wrong. An analogy will help explain why.